Mineralogy and Geochemistry of Rare Earth Elements in Manganese Deposits in the Anabanua District, Barru Regency, South Sulawesi Province, Indonesia - Wakila, Muhamad Hardin; Chalik, Citra Aulian; Thamsi, Alam Budiman; Jafar, Nurliah; Harwan; Umar, Emi Prasetyawati (UIR PRESS, 2025)
Research programmes on rare earth elements have not been widely carried out, especially on manganese deposits, even though manganese deposits also contain rare earth elements. Research on manganese mineralogy has been done before, however, research has not focused on rare earth metal elements found in manganese deposits, so further research is needed to find out the mineralogy, geochemistry, and gardes of rare earth metal elements in manganese deposits in the tropics. There are 3 methods of analysis at once, namely petrographic, XRD, and ICP-OES methods. The minerals found in manganese samples in the study area are: Albite, Chlorite, Plagioclase, Orthoclase, Quartz, Chlorite, Opaque, Pyrolusite, Muscovite, Diopside, Hematite, Rodochroite, Manganochromite and Manganite. Rare earth element levels in manganese deposits are Yttrium (8.7-35.5 ppm), Scandium (4-28 ppm), Lanthanum (5.3-122 ppm), Cerium (9.4-198 ppm), Praseodymium (1.3-23.6 ppm), Neodymium (690.9), Samarium (1.2-15. 4 ppm), Europium (0.6-3.5 ppm), Gadolinium (1.4-13.5 ppm), Terbium (0.241.75 ppm), Dysprosium (1.4-7.9 ppm), Holmium (0. 3-1.3 ppm), Erbium (0.8-3.2 ppm), Thulium (0.1-0.4 ppm), Ytterbium (0.8-2.4 ppm) and Lutetium (0.14-0.39 ppm). These results indicate that manganese deposits in Anabanua Village, Barru Regency, have the potential to be a source of LREE (La, Ce, Pr, Nd, and Sm) with concentrations exceeding those of several deposits around the world, making them worthy of consideration in strategic mineral exploration in Indonesia in general.